Realism and Representation in Philosophy and Cinema: A Critical Examination of Alfred Hitchcock’s The Wrong Man with Special Reference to André Bazin’s Theory - Mohammad Ghaffary; Melika Ramzi (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
The issue of “reality” and its representation in artistic works has been one of the major concerns of artists and theorists since classical times, which came to its climax in the mid-nineteenth century when following scientific advances and social changes, including the invention of photography, European painters and writers treated the issue more directly and precisely. This resulted in the formation of a movement named “Realism,” which aimed at recording external reality accurately and objectively, especially social reality and the condition of the lower classes. Alfred Hitchcock’s The Wrong Man (1957) is a narrative movie based on a true story and containing several Realist elements. The director claimed that it was a “documentary” faithfully representing truth, without any directorial interference. After a brief comparative account of the concepts of “reality” and “realism” in philosophy and cinema, the present study, adopting André Bazin’s theory of realism in the cinema, investigates the realistic dimensions of this movie to see whether, despite the filmmaker’s claim and the presence of certain realistic features, it can be ultimately regarded as a realistic work or not. The analysis of the movie shows that not only does The Wrong Man have subjective aspects, but it has not also been greatly faithful to the true incident and, thus, it does not correspond to Bazin’s conception. This discussion eventually leads to the question of whether, given the autonomous, external existence of objective reality, it is possible to represent it faithfully and impartially in artistic media.